Exploring learners' beliefs about science reading and scientific epistemic beliefs, and their relations with science text understanding. Issue 10 (2nd July 2016) - Yang, Fang-Ying; Chang, Cheng-Chieh; Chen, Li-Ling; Chen, Yi-Chun
ABSTRACT: The main purpose of this study was to explore learners' beliefs about science reading and scientific epistemic beliefs, and how these beliefs were associating with their understanding of science texts. About 400 10th graders were involved in the development and validation of the Beliefs about Science Reading Inventory (BSRI). To find the effects of reader beliefs and epistemic beliefs, a new group of 65 10th grade students whose reader and epistemic beliefs were assessed by the newly developed BSRI and an existing SEB questionnaire were invited to take part in a science reading task. Students' text understanding in terms of concept gain and text interpretations was collected and analyzed. By the correlation analysis, it was found that when students had stronger beliefs about meaning construction based on personal goals and experiences (i.e. transaction beliefs), they produced more thematic and critical interpretations of the content of the test article. The regression analysis suggested that students SEBs could predict concept gain as a result of reading. Moreover, among all beliefs examined in the study, transaction beliefs stood out as the best predictor of overall science-text understanding.